2019
DOI: 10.1002/ejlt.201900227
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Synthesis of 1‐Alkyl‐2‐hydroxy‐sn‐glycero‐2,3‐cyclic‐phosphate Using a Novel Lysoplasmalogen‐Specific Phopholipase D

Abstract: Many phospholipase Ds (PLDs) are known to catalyze transphosphatidylation as well as hydrolysis of phospholipids. Transphosphatidylation of lysoplasmalogen (LyPls)‐specific phospholipase D (LyPls‐PLD), which catalyzes hydrolysis of ether lysophospholipids such as LyPls and 1‐hexadecyl‐2‐hydroxy‐sn‐glycero‐3‐phosphocholine (Lyso‐PAF), still remains unclear. This study aims to reveal the transphosphatidylation activity of LyPls‐PLD, that is, the production of cyclic ether lysophospholipid. The enzymatic reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…However, such flexibility may also make it more difficult for the intermediate or product to dissociate from the catalytic pocket. This conclusion is supported by the fact that hydrolytic reaction with WT allowed the 100% cyclic product, 1‐hexadecyl‐2‐hydroxy‐ sn ‐glycero‐2,3‐cyclic‐phosphate, to be generated from LysoPAF, but not from LyPlsCho [7]. We also reported that the conformation of the sn ‐1 chain of the substrate was likely involved in substrate binding and product release, which represented the rate‐limiting steps of the reaction, thereby suggesting that substrate recognition may be strongly influenced by the conformation of sn ‐1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such flexibility may also make it more difficult for the intermediate or product to dissociate from the catalytic pocket. This conclusion is supported by the fact that hydrolytic reaction with WT allowed the 100% cyclic product, 1‐hexadecyl‐2‐hydroxy‐ sn ‐glycero‐2,3‐cyclic‐phosphate, to be generated from LysoPAF, but not from LyPlsCho [7]. We also reported that the conformation of the sn ‐1 chain of the substrate was likely involved in substrate binding and product release, which represented the rate‐limiting steps of the reaction, thereby suggesting that substrate recognition may be strongly influenced by the conformation of sn ‐1.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study of ours indicated that LyPls‐PLD shows 53% relative activity with 1‐hexadecyl‐2‐hydroxy‐ sn ‐glycero‐3‐phosphocholine (LysoPAF) than with LyPlsCho [7]. This increased activity level may be useful for conducting a lipoprotein‐associated phospholipase A 2 (Lp‐PLA 2 ) activity assay, as described below [8].…”
Section: Figmentioning
confidence: 99%